Prevalence of reading difficulties and attention deficit hyperactivity disorder in a sample of Spanish prisoners - Giménez, Almudena; Loredo, Mariana; Monge, Blanca; Sánchez, Pablo; López-Pérez, Javier (Revista de Investigación en Logopedia, 2025)
This is the first study examining prevalence and co-occurrence of reading difficulties and attention deficit hyperactivity disorder (ADHD) in a Spanish prison population. A main goal was to explore if prisoners’ reading problems were linked to an underlying phonological deficit or to insufficient schooling. The performance of 117 prisoners on reading, phonological, and rapid automatized naming (RAN) tasks were compared to that of 13-15-year-old secondary students. ADHD was assessed by two self-rating questionnaires. Results showed that prisoners were poorer readers but performed equally on the phonological tasks as the secondary students. These results suggest that lack of reading training and practice could account for prisoners’ low reading performance rather than a phonological deficit. In addition, students’ and prisoners’ prevalence of dyslexia was within the rate of the general population, while prisoners’ prevalence of ADHD was elevated. Finally, 67% of prisoners with poor reading, low phonological skills, or declared dyslexic exhibited comorbid symptoms of ADHD. This is taken as evidence that dyslexia itself may not be directly linked to involvement in antisocial behavior, but in combination with other conditions. Adequate schooling along with regular screening and intervention on learning difficulties could help to prevent the incidence of disturbed behavior or, in the case of conviction, to reduce the likelihood of recidivism.
Keywords: Attention deficit hyperactivity disorder; Dyslexia; Prisoners; Reading skills